Por meios e formas: o processo de edição crítica da partitura da Sonatina nº 1 de Dinorá de Carvalho - Machado, Ernane Júnior Ferreira (2024)
Dinorá de Carvalho (1895-1980), Brazilian composer and pianist, had a musical career marked by studies at the Dramatic and Musical Conservatory of São Paulo and further improvement in Paris with Isidor Philipp. Her oeuvre, which includes a variety of musical formations and styles, is catalogued in various brazilian institutions, with the main reference being the Coordination of Contemporary Music – CDMC, at UNICAMP, Campinas, SP. The research was motivated by the discovery that a significant part of her works remained in manuscript form and without phonographic record, representing a substantial challenge for musical practice and for the rescue of valuable musicological objects, such as the works of Dinorá de Carvalho. During the investigation, the Sonatina No. 1 for piano, dated 1949, was found to be one of the works without a phonographic reference and was in manuscript form, alongside other handwritten copies that presented discrepancies and probable transcription errors. Thus, the research was directed towards creating a critical edition of this work, aiming to promote the composer and facilitate the performance of the piece for all interested. The work involves transcribing the score, making editorial decisions, and preparing a critical apparatus. The oeuvre is divided into three chapters: the first addresses the biography of the composer, contextualising her trajectory and the composition of Sonatina No. 1. The second analyses the stylistic aspects of the work and comments on the history of the Sonata Form, providing a brief historical overview of the genre in Brazil and situating Dinorá de Carvalho’s Sonatina No. 1 within this context. The third chapter details the process of the critical edition of the work, from the collection of manuscripts to the final revised and digitised version by the author, followed by the final considerations.